Recorded and predicted butterflies in the Padang Bindu Karst, South Sumatra, Indonesia (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Qodri A, Encilia, Yulizah, Girmansyah D, Sunardi, Santoso W, Megawati, Rachmatiyah R, Fatimah, Darmawan, Sarino, Peggie D. 2023. Recorded and predicted butterflies in the Padang Bindu Karst, South Sumatra, Indonesia. Biodiversitas 24: 1057-1082. Padang Bindu Karst is one of the national cultural heritages in South Sumatra that has not been explored further for its faunal diversity, including the butterflies. Therefore, a preliminary survey of butterfly diversity of karst fauna outside the cave was carried out in the area for eight days. The aim was to analyze the butterfly diversity at an initial step, especially in the four main cave areas in the area, namely Harimau Cave, Silabe Cave, Putri Cave, and Candi Cave. Vegetation data based on their utility as host plants and/or nectar plants were also recorded to predict the number of butterfly species available in the area. There were 59 species of 157 individuals recorded, Eurema alithabeing the most abundant and followed by Junonia hedonia. From this preliminary survey, butterflies in the Padang Bindu Karst accounted for 35.75% of the total butterflies predicted to be there and 20.2% of the total butterflies recorded in South Sumatra. At least 12 species have not been recorded in South Sumatra, one of which is a rare species, namely Mahathala ariadeva, found in the secondary forest. Predicting the occurrence of butterflies based on the approach of host plants and nectar plants, as well as abiotic factors, is a butterfly conservation strategy that needs to be supported by long-term observations.
Keywords: Butterfly conservation, diversity, host plant, Mahathala arideva, nectar plant